Role of government policies to attain economic sustainability amid COVID-19 environment - Naqvi, Hasnain A. (Frontiers in Environmental Science, 2022)
The study is focused on analyzing the effects of Covid19 on the employment and businesses sectors. It also examined the various policies and actions that governments of selected countries took and can take to sustain the economic recovery. Although the pandemic has already caused unprecedented social and economic crises, it is still not over. The pandemic caused unprecedented health, economic environment, and social crises at the global level, however, several measures to curb the damages are underway, as the development of vaccines, immunization campaigns, job retention schemes, and financial support schemes to offset the worst economic impact of COVID-19. Under the current pandemic situation where new variants are still on the loose and causing trouble in many parts of the world, it is extremely important to maintain highly targeted support, especially towards the sustainable job market. Otherwise, bankruptcies and unemployment can make the economic recovery much harder. Strong economic policies can create and sustain jobs by supporting employers to avoid bankruptcies particularly for emerging and high-performing companies. To avoid experiencing the same issues that young people experienced during the global financial crisis, states should take immediate action to help them avoid falling behind. Concrete measures are required to sustain their connection with the education system and labor market.